2011
DOI: 10.1176/appi.ps.62.6.619
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Postpartum Depression Care Among Low-Income Women

Abstract: Objective The goal of this study was to characterize racial-ethnic differences in mental health care utilization associated with postpartum depression in a multiethnic cohort of Medicaid recipients. Methods In a retrospective cohort study, administrative claims data from New Jersey’s Medicaid program were obtained for 29,601 women (13,001 whites, 13,416 blacks, and 3,184 Latinas) who delivered babies between July 2004 and October 2007. Racial-ethnic differences were estimated with logistic regression for ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(100 citation statements)
references
References 35 publications
0
93
0
Order By: Relevance
“…[7,8,27] One study of women with GDM enrolled in Medicaid observed a higher incidence of depression as defined by ICD-9 coding or prescription drug claims. [7] This relationship was confirmed in studies of women with GDM who were examined using the Edinburgh Postnatal Depression Scale (EPDS) between 6 and 10 weeks postpartum [8] ; or the Center for Epidemiologic Studies-Depression Scale (CES-D) at 8 weeks postpartum. [27] However, in contrast to our study, these investigations did not document a clinical diagnosis of depression rather they evaluated depressive symptoms briefly postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8,27] One study of women with GDM enrolled in Medicaid observed a higher incidence of depression as defined by ICD-9 coding or prescription drug claims. [7] This relationship was confirmed in studies of women with GDM who were examined using the Edinburgh Postnatal Depression Scale (EPDS) between 6 and 10 weeks postpartum [8] ; or the Center for Epidemiologic Studies-Depression Scale (CES-D) at 8 weeks postpartum. [27] However, in contrast to our study, these investigations did not document a clinical diagnosis of depression rather they evaluated depressive symptoms briefly postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…In general, African American women report being less likely to seek treatment in formal mental health institutions and have much lower rates of treatment for postpartum depression and posttraumatic stress disorder in the perinatal period despite similar rates of illness. [21][22][23] Since African Americans have dramatically higher rates of perinatal loss than Caucasian women, it is critical that we identify culturally acceptable approaches to address unmet treatment needs in this population.…”
Section: Main Findingsmentioning
confidence: 99%
“…Postpartum depression affects 10–20 % of women (Kozhimannil et al 2011). Evidence has shown that African American women are more susceptible to postpartum depression due to factors such as financial hardship, chronic medical conditions, and stigma associated with mental illness (Boyd et al 2009).…”
Section: Mental Health and Parenting At A Young Agementioning
confidence: 99%
“…Adolescent mothers are at higher risk for postpartum depression compared to their adult counterparts, with estimates in adolescents ranging from 26 to 50 % (Nunes and Phipps 2013). Because detection and treatment rates are low among low-income minority women young minority mothers may be more vulnerable to underdiagnosis and inadequate mental health services (Kozhimannil et al 2011). …”
Section: Mental Health and Parenting At A Young Agementioning
confidence: 99%